KAUSALITAS BI RATE, INFLASI DAN INDEKS HARGA SAHAM - R. Adisetiawan . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
This study aims to analyze the causal relationships between variables of inflation, BI rate, and stock index and the effects of inflation and BI rate on the Indonesia Stock Exchange composite index. Samples taken are data from January 1995 to March 2012. The research data used are secondary data published by Bank Indonesia (BI) and the Capital Market Supervisory Agency and Financial Institution Supervisory Agency (Bapepam-lk) in the form of capital market statistics are then analyzed using Granger causality tests and Multiple Regression. The results of this study revealed that the 99% confidence level (a = 0.01); during the period 1995.1-2012.3 causal relationship exists between inflation, BI rate, and the Indonesia Stock Exchange composite index. The test results obtained by regression adjusted R-square value of 52.3%, this suggests that the movement patterns of stock price index in capital markets-related changes in various macroeconomic variables, one of which is a negative coefficient BI rate to Indonesia's capital market indices. The results also revealed that there was a very close relationship between the variables of inflation and BI rate to the CSPI, as evidenced by the magnitude of the correlation (R) of 72.6%.